163k views
2 votes
Find the quotient. simplify if possible q7÷q26q7÷q26

User Dseminara
by
4.5k points

1 Answer

2 votes


\bf q^7/ q^(26)q^7/ q^(26)\implies \cfrac{q^7}{1}/ \cfrac{q^(26)q^7}{1}/ \cfrac{q^(26)}{1}\implies \cfrac{\begin{matrix} q^7 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix} }{1}\cdot \cfrac{1}{q^(26)~~\begin{matrix} q^7 \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix} }\cdot \cfrac{1}{q^(26)} \\\\\\ \cfrac{1}{q^(26)q^(26)}\implies \cfrac{1}{q^(26+26)}\implies \cfrac{1}{q^(52)}\implies q^(-52)

User ChrisTorng
by
4.4k points